THE INFLUENCE OF PROFESSIONALISM, ETHICS, AND LOCUS OF CONTROL ON BPK RI AUDITOR PERFORMANCE - Simamarta, Jahormin; Sidauruk, Tagor Darius; Natrion (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2025)
The purpose of this study is to examine the influence of professionalism, auditor ethics, and locus of control on the performance of auditors at the Audit Board of the Republic of Indonesia (BPK RI). The population in this study consists of all auditors working at the BPK RI Central Office in Jakarta. The sample used in this study comprises 103 respondents selected from a total of 1,125 auditors. The research data is primary data obtained through questionnaire distribution. The sampling technique employed is purposive sampling with random sampling, while the data processing method used is multiple linear analysis with the assistance of SPSS version 21. The results of this study indicate that professionalism and auditor ethics have a partially positive and significant influence on auditor performance, whereas locus of control has a positive but not significant effect. Simultaneously, professionalism, ethics, and locus of control have a positive and significant effect on auditor performance, accounting for 30.90%. The remaining 69.10% is explained by other variables not included in this research model.